If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2x-51=(-2)=4x
We move all terms to the left:
2x-51-((-2))=0
We add all the numbers together, and all the variables
2x-49=0
We move all terms containing x to the left, all other terms to the right
2x=49
x=49/2
x=24+1/2
| 60=-6(1-5v)+6 | | x+2x+2x+3=73 | | 75x4=89 | | 4.5+0.9x=-6-2.6x | | y=2y=2 | | 3x+2(5x-1)=56.50 | | -23.5=3f-6f | | 2^x=2x+4 | | n/5-10=40 | | 34=-0.4(p=22) | | 7^(x+3)=15^(8x) | | 9^2=8(15+4x+3) | | 6=x(1-2x) | | 60÷x=13 | | x+2x+3+x+2x+3=78 | | 2(x+4)+7=25 | | 20+3x=2x | | 5.5a-0.5a+2.09=4.9a+2.6 | | (3x-1)^2=-12 | | -1.9k+0.7k=0.6k+2.34 | | 5x-10=10x+30 | | 0.2x+0.4x=165 | | m/5-m/8=3/2 | | m/5-m/8=3*2 | | 1=1/3x-3 | | (2580+2920)x=3000 | | 2x^2-88+14x=0 | | -1.9k=0.7k | | 6m=157 | | -4p-3=-9+7p | | 4x^2+15=-49 | | 14+5n=15 |